Stereodynamics of tetramezine - Kamuf, Matthias; Trapp, Oliver (Chirality, 2011)
The antidepressant drug tetramezine [1,2-bis-(3,3-dimethyldiaziridin-1-yl)ethane] consists of two bridged diaziridine moieties with four stereogenic nitrogen centers, which are stereolabile and, therefore, are prone to interconversion. The adjacent substituents at the nitrogen atoms of the diaziridines moieties exist only in an antiperiplanar conformation, which results in a coupled interconversion. Therefore, three stereoisomers exist (meso form and two enantiomeric forms), which epimerize when the diaziridine moieties are regarded as stereogenic units due to the coupled interconversion. Here, we have investigated the epimerization between the meso and enantiomeric forms by dynamic gas chromatography. Temperature-dependent measurements were performed, and reaction rate constants were determined using the unified equation of chromatography implemented in the software DCXplorer. The activation barriers of the epimerization were found to be ΔG≠ = 100.7 kJ mol−1 at 25°C and ΔG≠ = 104.5 kJ mol−1 at 37°C, respectively. The activation enthalpy and entropy were determined to be ΔH≠ = 70.3 ± 0.4 kJ mol−1 and ΔS≠ = −102 ± 2 J mol−1 K−1. Chirality, 2011. © 2010 Wiley-Liss, Inc.
Published online 15 September 2010
Dedicated to Prof. Dr. Günter Helmchen on the occasion of his 70th birthday
Gesehen am 07.07.2022